The negative effects of digital game playing on children's mental and physical health - Mustafaoğlu, Rüstem; Yasacı, Zeynal (Journal of Dependence, 2018)
Objective: The purpose of this research was to investigate the negative effects of digital games on children's mental and physical health.Method: One hundred thirty nine parents who have children aged 7-15 years were included. With the semi-structured assessment parents and children demographic information, age at which children start playing digital games, digital game playing time during the day, and the negative effects of playing digital games on children's mental and physical health of were questioned.Results: The mean age at which children started playing digital games was 4.5±1.6 years and duration of digital gaming during the day was 179.9±122.1 minutes. Duration of digital gaming during the day was higher in males and in the secondary school students. According to the parents, digital game playing in children caused mental problems such as digital game addiction (87.1%), anxiety and aggressive attitude (74.8%) and depression, asocialization (69.7%) and physical health problems such as musculoskeletal problems (72.5%), dryness, pain and redness in the eyes (70.0%) and deterioration in sleep quality (62.2%).Conclusion: Digital game playing in children may cause mental health problems such as anxiety and aggressive attitudes and depression and physical health problems such as musculoskeletal problems, dryness, pain and redness in the eyes, and deterioration in sleep quality.
Keywords: digital games; technological devices; addiction; child; health problems